What do Elementary School Teachers Think About 6Cs? - Poppy Anggraeni; Dadang Sunendar; Bunyamin Maftuh; Wahyu Sopandi; Ryan Dwi Puspita (Mimbar Ilmu, 2023)
21st-century skills are very important to be instilled in every learning process in elementary schools. Teachers must have the view that is instilling the 6 Cs. This study aims to analyze elementary school teachers' perceptions regarding 21st-century skills, especially the 6 Cs in learning in elementary schools. The method used in this research is the descriptive method. The research subjects were obtained randomly, namely as many as 71 elementary school teachers. The research instrument used a questionnaire in the form of a Google form. The data obtained were then analyzed, and the categories were determined. The results showed that elementary school teachers' perceptions of the knowledge aspect, namely 21st-century skills, must be owned and instilled in students in the 21st century, which is very high. In the aspect of understanding, the teacher's perception of the reasons for the importance of the 6 Cs instilling in elementary school students is also very high. In the implementation aspect, teachers have a high perception of instilling the 6 Cs in elementary school learning, either through innovative learning models or through interactive learning media.